Long noncoding RNA lncGALM increases risk of liver metastasis in gallbladder cancer through facilitating N‐cadherin and IL‐1β‐dependent liver arrest and tumor extravasation. Issue 7 (10th November 2020) - Li, Huaifeng; Hu, Yunping; Jin, Yunpeng; Zhu, Yidi; Hao, Yajuan; Liu, Fatao; Yang, Yang; Li, Guoqiang; Song, Xiaoling; Ye, Yuanyuan; Xiang, Shanshan; Gao, Yuan; et al.
Abstract: Background: Long noncoding RNAs (lncRNA) represent significant factors of the mammalian transcriptome that mediates varied biological and pathological processes. The liver is the most common site for gallbladder cancer (GBC) distant metastasis and contributes to the majority of GBC‐related death. How lncRNA affects GBC metastasis is not completely understood. Results: A novel lncRNA termed lncGALM (lncRNA in GBC associated with liver metastasis) was discovered to be highly expressed in cancer patients and xenografted tumors with liver metastasis. Elevated lncGALM in GBC patients also correlated to decreased survival. Invasion and migration of GBC cells were enhanced through lncGALM, both in vitro and in vivo. lncGALM functioned as sponges by competitively binding to and inactivating miR‐200 family members, which increase epithelial‐mesenchymal transition‐associated transcription factor ZEB1 and ZEB2, leading to a fibroblastic phenotype and increased expression of N‐cadherin. In addition, lncGALM bound to IL‐1β mRNA and stabilized the IL‐1β gene that mediates liver sinusoidal endothelial cell (LSECs) apoptosis. lncGALM‐expressing LiM2‐NOZ cells acquired a strong ability to migrate and adhere to LSECs, promoting LSECs apoptosis and therefore facilitating tumor cell extravasation and dissemination. Conclusions: lncGALM promotes GBC liver metastasis by facilitating GBC cell migration, invasion, liver arrest, and extravasation via the invasion‐metastasis cascade. Targeting lncGALM may be protective against the development of liver metastasis in GBC patients. Abstract : (1) This study documents a novel lncRNA‐lncGALM from the lncRNA expression profiles of human GBC samples and animal models. (2) lncGALM promotes EMT in GBC cells by binding to miR‐200 family members. (3) lncGALM facilitates extravasation and liver colonization of GBC cells. (4) lncGALM could serve as a therapeutic target of GBC.